(untitled) (Cultura Económica, 2019)
Starting from Argentina’s crisis in late 2001 and early 2002, the author examines the steps that led to convert the downturn in unexpected growth. Thus, the components of this growth with its strengths and weak points are detailed. Besides, the author presents and describes the fundamentals of the model: competitive exchange rate, monetary policy and twin surpluses. Finally, the challenges to overcome are analyzed, mainly the fight against inflation. The author concludes sustaining that, despite the existing social tension, the possibility of greater openness to dialogue, with a favorable world situation, will enable the country to transit the road of sustainable development in the medium term.